HUBUNGAN KEBIASAAN MENCUCI WAJAH DENGAN KEJADIAN ACNE VULGARIS PADA MAHASISWA KEDOKTERAN - Dhandi Mahardika Hidayat; Riri Arisanty Safrin Lubis; Nita Andrini; Irfan Darfika Lubis (Nusantara Hasana Journal, 2026)
Acne vulgaris is a common skin disorder among medical students. Proper facial cleansing habits may influence the occurrence of acne vulgaris. To examine the relationship between facial cleansing habits and the occurrence of acne vulgaris among 2022 cohort students at the Faculty of Medicine, University of Muhammadiyah North Sumatra. This analytic cross-sectional study involved 156 students enrolled through consecutive sampling. Facial cleansing habits were assessed using a validated closed-ended questionnaire, while acne vulgaris occurrence was determined through direct clinical inspection by a dermatology specialist. Data were analyzed using Chi-Square test at significance level p < 0.05. A total of 55.8% demonstrated adequate facial cleansing habits, while 41.0% experienced acne vulgaris. Statistical analysis indicated a significant association between facial cleansing habits and acne vulgaris occurrence (p = 0.012). There is a significant relationship between facial cleansing habits and acne vulgaris occurrence. Proper facial cleansing habits may serve as a practical non-pharmacological strategy to prevent acne vulgaris.